The Femoral Geometrical Measurements in Postmenopausal Turkish Women - H. T. Çalış; M. Eryavuz; M. Çalış; G. Can (Türk Osteoporoz Dergisi, 2002)
Femoral geometric measurements have been suggested to be important in the evaluation of the risk of osteoporotic hip fracture. The aim of this study was to determine the normal values of femoral geometric measurements in Turkish women. 232 women were selected by using suitable sample procedure to reflect Turkish women normal values (%95 interval of confidence). All of them were over 50 years of age postmenauposal women and none have had history of hip fracture. Hip axis length (HAL), femoral neck axis length (FNAL), acetabular width (AW), femoral head width (FHW), femoral neck width (FNW), femoral shaft width (FSW), intertrochanteric width (ITW), cortical bone thickness of the medial femoral neck (NMCT), medial femoral shaft cortical bone thickness (SMCT), lateral femoral shaft (SLCT), cortical bone thickness, femoral neck-shaft angle in degrees (N-SA) were measured bilaterally on standart AP plain pelvic X-ray radiograms. In the subjects mean age , weigth,heigth and body mass index (BMI) were 62.5±7.4, 70.84±12.5, 157.5±6.7, 28.58±4.9 respectively. Mean values of femoral geometric measurements for right and left hip respectively were fallows: HAL:130.5±8.9, 130.1±9.0 ; FNAL: 112.7±6.9, 112.5±6.9 ; FHW:53.3±3.2, 53.0±3.4; FNW:35.8±2.8, 35.9±2.7; FSW:37.6±3.0, 37.7±3.1; ITW: 62.5±5.3, 63.0±3.9; NMCT: 2.1±0.7, 2.0±0.6; SMCT: 7.8±1.4,7.1±1.3; SLCT: 7.0±1.3, 7.1±1.3; N-SA: 128.9±5.9, 128.9±5.8.There were no statistically significant difference between right and left measurements. We think that these values are representatives of Turkish women and similar to the values of Caucasian women according to the literature.